Atypical Cogan's Syndrome - João Queirós; Sofia Maia; Mariana Seca; António Friande; Maria Araújo; Angelina Meireles (Case Reports in Ophthalmological Medicine)
Background. Cogan’s syndrome is a rare clinical entity whose etiopathology is still unknown, and the treatment strategies are not clearly defined. Case. A 23-year-old male presented with symptoms of headache, peripheral facial palsy, persistent right hearing loss and bilateral papillitis. Workup excluded all infectious, granulomatous, neoplastic, and immune causes. The diagnosis of atypical Cogan’s syndrome was established, and the patient was treated with systemic corticosteroids and later on with cyclophosphamide and methotrexate. There were improvement of visual symptoms and stabilisation of left hearing. Conclusion. Cogan’s syndrome is a very rare disease with no specific biological tests for the diagnosis. The diagnostic exams are mostly important to exclude other etiologies. The atypical ocular and audiovestibular manifestations make the diagnosis difficult, delaying the institution of appropriate therapy which may result in profound bilateral deafness.